The influence of educational service quality on parent and student satisfaction in Private High School X, Bandung City - Slamet, Yehezkiel Bobby; Saputra, Bobby Wiryawan (International Journal Labs, 2024)
The purpose of this study is to determine the influence of the quality of educational services on the satisfaction of students and parents of students at private high school X, Bandung City. This research was conducted in West Java Province, especially at Senior High School (SMA)